THE EFFECT OF KAFFIR LIME (CITRUS HYSTRIX) ESSENTIAL OIL ON BEHAVIOR AND MORTALITY OF Aedes aegypti LARVAE - Ririh Jatmi Wikandari; Surati Surati (Poltekkes Kemenkes Semarang, 2020)
DHF vector control still uses chemicals. Long-term application can lead to target insect resistance and environmental pollution so that a better alternative is to use biological insecticides because it is environmentally friendly. The aim of the study is to identify the effect of kaffir lime peel essential oil on the behavior and mortality of Ae.aegypti larvae. The research method used was completely randomized design of three treatments and three replications. The results show that larval behavior after administration of kaffir lime peel essential oil at a concentration of 103 ppm decreased the frequency of movement, the larvae were unable to rise to the surface of the water after 1.5 hours. The results of the research were tested with probit analysis at a confidence level of 95% LD 263,552 ppm. The analysis result in one-way ANOVA for the number of differences in the number of dead larvaes, with the value obtained sig. = 0.000, which means that there is a significant influence on differences in doses of papaya seeds powder solution used against the death of Ae. aegypti larvaes. Kaffir lime peel contains essential oils that can be used as biological insecticides in DHF vector control.